Rekolekcje i kongregacje dekanalne duchowieństwa w diecezji augustowskiej czyli sejneńskiej - Jemielity, Witold (Prawo Kanoniczne, 2002)
In the 19 th century commonly there were retreats and meetings of the clergy in deaneries. The Apostolic See, synods and bishops regularized the style of their being conducted. In the principality of Warsaw Kingdom the regulations laid down by Cardinal Maciejewski in the year 1601 were those essentially binding. In the course of these meetings of the clergy of the Diocese of Augustów or of Sejny, there was greatly felt the impact of the statutes of the Synod of Plock in the year 1733, and the decrees of Bishop Poniatowski of Plock given at the end of the 18 th century. After the January uprising the civil authorities restricted the taking place of retreats and meetings. Retreats lasted five or three days and had a totally prayerful character. The local dean led them. There were separate groups for pastors and for their curates. With the retreats was conjoined the juridical right to hear confessions in the following year. On the day prior to the retreats, the priests took examinations on previously determined theological subjects. The retreats primarily took place in monasteries. The fundamental goal of the meetings was the continued instruction of the parish clergy. During the portion of the meeting dedicated to prayer one Holy Mass was offered for the deceased priests of one’s deanery, and a second to the Holy Spirit. T he faithful at this time went to confession and listened to the homilies. In the second portion of the meetings, only clergy took part. The clergy presented researched papers on theological questions and likewise evaluated their activities and discussed current pastoral problems. The meetings lasted one day and took place successively in their various parishes.